Interpreting WTO agreements : problems and perspectives / Asif H. Qureshi. - Qureshi, Asif H. (Asif Hasan), 1956- (Cambridge University Press, 2006)
This book was first published in 2006. The case law of the World Trade Organization is now extensive, running into over one hundred cases and thousands of pages. The interpretative process involved in this jurisprudence constitutes a form of legislative activity, and is therefore of great significance not only to the parties to disputes, but to the membership of the WTO. Qureshi sets out here to identify some of the underlying problems of interpreting WTO agreements, within the context of different issues, problems, objectives and disciplines, and to comprehensively examine the underlying conditions for the interpretation of WTO agreements. He focuses on: the apparatus of interpretation in the WTO; the manner of interpreting institutional norms, national measures, and exceptions; the manner of facilitating the development objective; the manner of reconciling conflicting norms through interpretation; and finally the manner of interpreting the trade remedies agreements. Various perspectives on interpretation are proffered, particularly that of justice and development.